Stratigraphy, age and paleomagnetism of Langidalur, northern Iceland (Dataset) ... - Kristjánsson, Leó; Jóhannesson, Haukur; McDougall, Ian (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Stratigraphy, age and paleomagnetism of Langidalur, northern Iceland ...